Synthesis Of Gold Nanorods Using The Seed Mediated Method And Its Conjugation With Antibody For Diagnostics Applications - Teoh, Poay Ling (2012)
This work describes the synthesis of gold nanorods (AuNRs) produced using the citrate seed mediated method and cetyltrimethylammonium bromide (CTAB) seed mediated method. The AuNRs are conjugated with antibody for diagnostic applications. The synthesis of AuNRs via the seed mediated method involves two consecutive stages: preparation of seed solution and growth stage. The AuNRs were formed upon the addition of seed solution into the growth solution. By comparing the yield of AuNRs synthesized from both type of seed solutions, it was found that higher yield and longer AuNRs was produced by using CTAB seed solution. Meanwhile, the properties of AuNRs were also influenced by the synthesis parameters of the growth solution such as concentration of silver nitrate (AgNO3), concentration of CTAB, concentration of ascorbic acid, volume of seed solution and volume of nitric acid (HNO3). Among these samples, the optimum synthesis parameters to produce AuNRs were 0.2 M CTAB, 0.08 M ascorbic acid, 50 l seed solution and 300 μl HNO3 via CTAB seed mediated growth method. The optimum synthesis parameters produced 4.9 aspect ratio of AuNRs. The performance of AuNRs conjugated mouse anti-human IgG4 was successfully checked using an immunochromatographic (ICG) strip assay. From the test strip result, the intensity of the control line increased with increasing the amount of mouse anti-human IgG4. The result showed that the covalent attachment between AuNRs and mouse anti-human IgG4 exhibited the best conjugation.